2002
DOI: 10.1097/00010694-200212000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Surface Chemical Properties of Soil Using Flow Calorimetry 1

Abstract: Flow calorimetry, which is ideally suited for measuring reactions oc curring at the liquid/solid interface, has been used to study the surface chemistry of many types of solids, but little use of it has been made in the study of surface reactions of soils. The purpose of this study was to demonstrate the application of flow calorimetry to the study of two fun damental soil chemical processes, namely cation exchange and phosphate sorption. Surface horizon samples of a Typic Acrorthox and a Typic Tropohumult fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…Isothermal titration calorimetry data can be used to somewhat distinguish between these mechanisms. For example, exothermic (producing heat) reactions regarding P sorption in neutral and acid soils indicate ligand exchange mechanisms onto Al and Fe minerals and kaolinite (Appel et al, 2013;Penn and Zhang, 2010;Rhue et al, 2002;Harvey and Rhue, 2008). On the other hand, endothermic (absorbing heat) reactions indicate precipitation of Al and Fe phosphates (Penn and Warren, 2009;Rhue et al, 2002).…”
Section: Calorimetry As An Indicator Of Phosphorus Sorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isothermal titration calorimetry data can be used to somewhat distinguish between these mechanisms. For example, exothermic (producing heat) reactions regarding P sorption in neutral and acid soils indicate ligand exchange mechanisms onto Al and Fe minerals and kaolinite (Appel et al, 2013;Penn and Zhang, 2010;Rhue et al, 2002;Harvey and Rhue, 2008). On the other hand, endothermic (absorbing heat) reactions indicate precipitation of Al and Fe phosphates (Penn and Warren, 2009;Rhue et al, 2002).…”
Section: Calorimetry As An Indicator Of Phosphorus Sorptionmentioning
confidence: 99%
“…For example, Aharoni and Sparks (1991) describe sorbate transport processes in a solid-liquid system with several scenarios: transport of sorbate in the soil solution, transport across a liquid film at the solid-liquid interface, transport in a liquid-filled micropore, and diffusion of a sorbate at the soil surface or into a micropore. The "slow burn" (Rhue et al, 2002) displayed by the Clear Creek soil has been observed in other studies (Kabengi et al, 2006b;Harvey and Rhue, 2008). Since both soils were dominated by ligand exchange chemical mechanisms which are extremely fast (Sposito, 1994) explanation for the long "slow burn" for P sorption in the Clear Creek soil is that after the initial P sorption reactions occurred on the surfaces of minerals, further P sorption occurred only after the slow physical transport and diffusion of P into micropores (micropore scale physical nonequilibrium).…”
Section: Calorimetry As An Indicator Of Phosphorus Sorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heats (DH ) of Pb, Cu, and Zn sorption onto PR were determined using flow calorimetry Rhue et al, 2002). Amounts of 120 G 0.5 mg of PR (0.25e0.50 mm) were placed in the column of the flow calorimeter.…”
Section: Calorimetric Measurementsmentioning
confidence: 99%
“…This helps to better un derstand the binding strength of a particular reactive species onto the solid surface. Flow calorimetry has been used to study the surface chemistry of solids Rhue et al, 2002), but no study has been conducted on the surface reaction of metals with phosphate minerals.…”
Section: Introductionmentioning
confidence: 99%